(untitled) (MIST International Journal of Science and Technology, 2023)
Although Terracotta is one of the oldest in almost all sub-continents and was spread out across the whole world now-a-days it has been a common, traditional, and indigenous object in Bangladesh for everyday life. Inspired by the religion or rituals, terracotta art has evolved in many ways in Bengal over time. From Babylon walls to high-performance rain screens, terracotta claddings have proven repeatedly to be technologically superior and aesthetically rich. Realizing the evolution of terracotta prepares architects to add new, creative chapters to a superior history. Through an extensive inventory of recent examples, project case studies and architectural details, this study provides a foundation for understanding the nature of the material and the opportunities it offers in the urban life. The objective of the paper is to know the evolution of terracotta as a historic, artistic and cultural materials and shapes of objects with aesthetical and technical aspects that plays an important role for place making in both exterior and interior of architectural design and building practice. The paper explores the evolution of terracotta in Bangladesh and prepares architects and builders to make new, creative uses of the timeless material. Validating the examples of expressive possibilities, this precious study can be an inspiration for students and professionals alike who are interested in creating sustainable spaces by using visual and cultural components. MIJST, Vol. 11, December 2023 : 53-60 DOI: https://doi.org/10.47981/j.mijst.11(02)2023.412(53-60)